Human behavior in organizations - Martires, Conception Rodil (Manila, 1992)
The content of this textbook can be covered in one semester. It includes foru main areas: Fundamentals of human behavior, motivation, needs and values; communication; and leadership. The individual is the focus of the discussion leaving much of group and organization as dimensions for deeper analysis in the graduate program
Keywords: organizational behavior